(untitled) (Andamios, Revista de Investigación Social, 2014)
The domain that was exercised by the Royal Spanish Academy on non academic dictionaries, mainly in the treatment of the Spanish of the spanish-speaking Latin-american countries, along with the evolution that took the Latin-american spanish, prevented a substantial progress in the overall spanish lexicography at both sides of the Atlantic, which broke with the emergence of national dictionaries, the peninsular spanish and Mexican spanish, during the twentieth century, and the national of argentinian spanish, during the XXI. Knowledge of this situation and the assessment of dictionaries, particularly as containers of social memory and cultural values of a community, is the main contribution of this article.